Algoritma Sequential Search dan Hashing pada Aplikasi E-Lapor Layanan Publik Rukun Tetangga - Pandyawan Eka Rizqullah; Ratih Titi Komala Sari (Universitas Indraprasta PGRI Jakarta, 2022)
Rukun Tetangga is one of the public services in Indonesia, Rukun Tetangga provides services to residents for the peace of local residents. At this time the data management process for the Neighborhood Association is currently running as usual, there are several problems identified, namely difficulties in finding data because it is still stored in the form of an agenda book, making letters which must take a long time because they are still recorded manually. The purpose of this final report is to design an application for the Rukun Tetangga public service using a Sequential Search and Hasing Algorithm while the programming language used is HTML, PHP, CSS and for the database using a website-based MySQL. The results of this study indicate that the use of the Rukun Tetangga public service application can assist population data collection in managing population movement data and making correspondence for the benefit of residents in completing certain affairs and according to what the Head of the Rukun Tetangga expects. Quality test results using microtime and blackbox to expect more effective results to use.